The Temple in early Christianity: experiencing the sacred - Regev, Eyal (The Anchor Yale Bible Reference Library, 2019)
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Preface -- Editions and Translations -- Introduction -- Chapter 1. Jesus: "Cleansing," Trial, and Last Supper -- Chapter 2. Paul's Letters: Temple Imagery as Religious Identity -- Chapter 3. Mark: Criticism or Rejection? -- Chapter 4. Q and Matthew: The Sacred Temple -- Chapter 5. Luke-Acts: Living and Dying with the Temple -- Chapter 6. The Gospel of John: Temple and Christology -- Chapter 7. The Book of Revelation: The Alternative Temple -- Chapter 8. Hebrews: The New Heavenly Temple Cult Based on the Old One -- Chapter 9. Relating to Judaism, Experiencing the Sacred -- Chapter 10. Concluding Thoughts -- Notes -- Bibliography -- General Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- W -- Y -- Z -- Index of Ancient Sources.